Food variety of lesser whistling duck in Malaysian lakes - Martins, Chukwuemeka Onwuka; Rajpar, Muhammad Nawaz; Zakaria, Mohamed (Universiti Putra Malaysia Press, 2020)
Food distribution and diversity is a significant factor that determines the habitat and site selection of avian species. Its effects on the health, reproduction, survival rate, diversity indices, population structure and home range of avian species. In wetland ecosystem, bird home range and population structure is influenced by richness and diversity of food resources and availability of suitable foraging sites. The aim of the study was to ascertain the food variety of Lesser Whistling Duck – Dendrocygna javanica in Paya Indah Wetland Reserve (PIWR). A scan method was employed from strategic places or blinds using a spotting scope and binocular to determine the food selection and density by Distance sampling point count method. Food items were categorised into the aquatic plants (AP), aquatic invertebrates (AIV), aquatic vertebrates (AV), terrestrial plants (TP), terrestrial vertebrates (TV) and terrestrial invertebrates (TIV). Distance analysis indicated that PIWR harboured 3.88 ± 0.00 birds per ha (n = 188 individuals). In addition, the results revealed that higher bird relative abundance of Lesser Whistling Duck concentrated in the shallow of Belibis lake that was rich in submerged and emergent vegetation (Eleocharis dulcis, Philydrum lanuginosum, Utricularia vulgaris, and Potamogeton perfoliatus). Kruskal–Wallis H test showed that food items were significantly different. Lesser Whistling Duck showed strong correlationship with AIV (r2 = 1.00, P < 0.05) and negative relationship with water TP (r2 = –0.061, P< 0.05). The regression model highlighted that Lesser Whistling Duck significantly preferred aquatic invertebrates, r2 = –0.686±0.68; P <0.001 and aquatic vertebrates, –0.459±0.26) than other food items. The results revealed that shallow marshybased lakes rich in aquatic vertebrates and invertebrates harboured higher population of Lesser Whistling Ducks to utilize it and performed multiple activities than other habitats.